1999
DOI: 10.2527/1999.7761322x
|View full text |Cite
|
Sign up to set email alerts
|

Sire marbling score expected progeny difference and weaning weight maternal expected progeny difference associations with age at first calving and calving interval in Angus beef cattle.

Abstract: Field records from the American Angus Association were used to study the associations of sire marbling score EPD and sire weaning weight maternal (milk) EPD with age at first calving (AFC) and calving interval (CI). Cows were selected based on the accuracy of their sire's milk (> or =.7) or marbling (> or =.6) EPD. The data were screened using biological constraints, and regression models were used to identify records that were greater than 5 SD from the mean. The AFC was modeled for both milk and marbling dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 12 publications
4
21
2
2
Order By: Relevance
“…Factors affecting CI The mean CI of 404 days observed for DMBB cows in this study was considerably longer than reported for most other beef breeds (Osoro and Wright, 1992;Frazier et al, 1999; Fiems and Ampe Pilarczyk and Wójcik, 2008). Reasons for the reduced reproductive performance are related to the double-muscling phenomenon (Fiems, 2012).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Factors affecting CI The mean CI of 404 days observed for DMBB cows in this study was considerably longer than reported for most other beef breeds (Osoro and Wright, 1992;Frazier et al, 1999; Fiems and Ampe Pilarczyk and Wójcik, 2008). Reasons for the reduced reproductive performance are related to the double-muscling phenomenon (Fiems, 2012).…”
Section: Discussioncontrasting
confidence: 47%
“…Hanzen et al (1994) reported an average CI of 435 days in suckled DMBB cows compared with 364 days for Blue-Grey cows (Osoro and Wright, 1992), 370 days for Angus cows (Frazier et al, 1999), 377 days for Simmental cows, 387 days for Salers cows, 381 days for Limousin cows and 393 days for Hereford cows (Pilarczyk and Wójcik, 2008). It averaged 364 days for Charolais and Limousin multiparous cows, and 385 and 389 days, respectively, for Charolais and Limousin primiparous cows (Agabriel et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Por el contrario, Frazier et al (1999) con ganado Angus, Oyama et al (2002) con ganado Japonés Negro y Azevêdo et al (2006b) con ganado Nelore encontraron que intervalo entre partos es escasamente heredable con valores de 0,03, 0,05 y 0,05, respectivamente. Se ha reportado que bajos estimadores de heredabilidad para intervalo entre partos se pueden deber a: 1) la poca disponibilidad de animales en la estimación, 2) la fuerte influencia ambiental sobre la característica, 3) la necesidad de ajustar mejor los efectos fijos, y 4) al uso de modelos que no pueden explicar adecuadamente la estructura de la población evaluada (Goyache y Gutiérrez 2001).…”
Section: Intervalo Entre Partosunclassified
“…A lower AFC has a positive impact on both economic and breeding aspects of cattle production, such as reduced costs of raising heifers and reduced female generation interval. Despite the importance of AFC, many breeding programs do not include this trait in the breeding goal because of its low heritability, sex-limited expression and antagonistic relationships with production traits (Frazier et al, 1999;Nogueira, 2004, Forni andAlbuquerque, 2005;Pereira et al, 2006).…”
Section: Introductionmentioning
confidence: 99%